2014
DOI: 10.1111/jse.12094
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history and underlying adaptation of alpine plants on the Qinghai–Tibet Plateau

Abstract: As the highest and largest plateau in the world, the Qinghai-Tibet Plateau, with its numerous endemic species, is one of the important alpine biodiversity hotspots. Only recently have the evolutionary histories and underlying adaptations of these alpine plants become clear, through research mostly based on testable experiments and analyses. In this issue, we collected a total of 13 papers related to such aims. In addition, we selected a few published papers to highlight the major findings in the recent past. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
184
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(187 citation statements)
references
References 86 publications
(107 reference statements)
3
184
0
Order By: Relevance
“…In such situations, independent genetic lineages appeared in different plateau regions due to isolations among developed ice sheets. However, although earlier investigations focused on species that populate the eastern, central and northern portions of the QTP, few involved plants were found in the western part of that plateau (Qiu et al, 2011;Liu et al, 2012Liu et al, , 2014.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In such situations, independent genetic lineages appeared in different plateau regions due to isolations among developed ice sheets. However, although earlier investigations focused on species that populate the eastern, central and northern portions of the QTP, few involved plants were found in the western part of that plateau (Qiu et al, 2011;Liu et al, 2012Liu et al, , 2014.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, because the QTP was most sensitive and vulnerable to the Pleistocene global climate (Zhang, 1983;Raymo and Ruddiman, 1992;Zhan, 2005), growth, reproduction, and survival of existing species have depended greatly upon exposure to suitable temperatures (Zheng, 1996;Ni, 2000;Thompson et al, 2000). Therefore, it is a very favorable area to study the evolutionary histories of plants in response to previous climate change (Bawa et al, 2010;Liu et al, 2012Liu et al, , 2014.…”
Section: Introductionmentioning
confidence: 97%
“…Mountains in the QTP with the potential to act as barriers to movement can result in genetic structures ranging from panmixia (Lessios et al, 2003) to complete separation (Baums et al, 2012). Therefore, species on the QTP likely experienced an evolution history different from other areas of the world (Liu et al, 2014; Wen et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…We did not calibrate these divergences due to the lack of the reliable fossils and mutation rate. However, numerous studies of species diversification for other genera suggested the rapid uplifts of the Qinghai-Tibet Plateau since the Miocene and the subsequent climate change should have caused habitat fragmentation across China, which had probably triggered allopatric speciation in numerous genera occurred there (Liu et al, 2002(Liu et al, , 2006(Liu et al, , 2012b(Liu et al, , 2014bXu et al, 2010;Liu et al, 2013). In addition, all detected mitotypes or chlorotypes should have produced before the last glaciation maximum (LGM, around 18e21 Ka BP) of the Quaternary.…”
Section: Interspecific Relationships and Allopatric Divergence Of Thementioning
confidence: 98%
“…However, discrimination power for species identification based on sequence variations will change dependent on the geographic isolations and possible speciation ages. In addition to test this hypothesis, our range-wide sampling and two large population genetic datasets based on cytoplasmic DNA variation undoubtedly will aid to understand the interspecific relationship of these species and their response to the historical climate changes (Liu et al, 2012b(Liu et al, , 2014bHao et al, 2015).…”
Section: Introductionmentioning
confidence: 98%